Action research to improve water quality in Canada's Rideau Canal: how do local groups reshape environmental governance?. Issue 5 (4th May 2021) - Mistry, Isha; Beaudoin, Christine; Kotecha, Jyoti; Evans, Holly; Stevens, Manuel; Vermaire, Jesse C.; Cooke, Steven J.; Young, Nathan
ABSTRACT: The historic Rideau Canal, spanning 200 km between the Canadian cities of Ottawa and Kingston, is a world heritage site and recreational waterway. The waterway presents a governance challenge, with multiple jurisdictions and agencies responsible for its management, making it difficult to establish a common vision to address environmental issues. Local stakeholders are concerned about toxic algal blooms in the downstream section of the Canal (the Lower Cataraqui region) because these blooms limit use of the system and pose a potential threat to human and environmental health. In the absence of a strategy to effectively manage water quality, a grassroots group called the Three Lakes Water Quality Group (TLG), has brought various stakeholders together to initiate transdisciplinary discussions and find solutions. This article presents findings from action research with the TLG. Specifically, it examines (1) the activities and concerns of the TLG in the governance arena, (2) the views of local stakeholders on social-ecological issues, (3) the potential of using collaborative systems thinking to capitalise on the TLG's activities. Our analysis is informed by interviews and a workshop. We recommend that the TLG mobilise collaborative systems thinking when meeting with other stakeholders to discuss raising awareness, enforcing policy and producing knowledge about water quality issues in the region. These findings have implications for the entire Rideau Canal and other historic waterways by revealing the potential of local residents to initiate dialogue and drive future co-governance efforts.